Additive Allometric model of Populus sp. Single-Tree Biomass as a Basis of Regional Taxation Standards for Eurasia - Usoltsev, Vladimir Andreevich; Shobairi, Seyed Omid Reza; Tsepordey, Ivan Stepanovich; Chasovskikh, Viktor Petrovich (Indian Forester, 2019)
When using the terms of the volume of database on the level of singletrees of the genus Populus sp., the trans-Eurasian additive allometric models of biomass of for Eurasian Populus trees are developed for the first time, and thereby the combined problem of model additivity and generality is solved. It is harmonized in two ways: it eliminated the internal contradictions of the component and the total biomass equations, and in addition, it takes into account regional differences of trees of equal sizes not only on total, aboveground and underground biomass, but also on its component structure, i.e. it reflects the regional peculiarities of the component structure of tree biomass.